Analisis Jejaring Pelaku Pariwisata di Kabupaten Bintan : Studi pada Event Ironman Bintan - Dewi Nurwati Dewi; Adji Suradji Muhammad; Eka Suswaini (Jurnal Sociohumaniora Kodepena (JSK), 2020)
Analysis of Tourism Actors Network in Bintan Regency. This study aims to determine the network of tourism actors in Bintan Regency through the Ironman Bintan event in 2019. The problem formulation in this study is "How is the network of tourism actors in Bintan Regency through the Ironman Bintan event in 2019." This research uses descriptive analysis with a qualitative approach. The focus of the research is based on Damanik and Weber's theory of tourism actors, namely tourists, tourism service providers or industries, tourism service supporters, the government, local society, and Non-Government Organizations (NGOs). The data collection technique is done by studying literature. Data that has been obtained is analyzed using interactive data analysis. The results showed that the networking carried out by tourism actors through the Ironman Bintan event in 2019 was able to increase tourist visits to Bintan Regency with the role of each stakeholder.